Analisis Makna Bahasa dalam Prosesi Kesenian Jaran Jenggo Aswo Kaloko Joyo dalam Tradisi Khitanan - Abdullah Zawawi; Abd. Had (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2021)
Jaran Jenggo Art is a traditional art of the Solokuro Village community that has long lived and developed in the community of its supporters. This art is a procession of art combined with attractions performed by horses and handlers. This study aims to determine the signs, symbols, and meanings contained in Jaran Jenggo art. Secondary data is obtained from several literature literature. Such as books, internet sites, and others related to the object of a research. This study uses a qualitative approach. Search data process begins with observing participation in Jaran Jenggo art performances in Solokuro Lamongan Village. Search data was carried out starting Agusts 27 - Oktober 28 2020. This study used in-depth interviews with art owners Jaran Jenggo, teams, and spectators. The results of this study discuss the signs, symbols, and meanings of each activity process using semiotic studies.